(3OGFQ GdCUhd Edi Yde GdCUhds - (3GdgQhj, GHf eHGQc TGgs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj Sbi dCUhd GdeSJfHWjf ef chKQ ZQGFH Gdeaghe eGkA hLYd HQaQa QCaJg eTGQY GdTQY cGdQhV GdCQjV cdGhI CeG HYO aEf cJGHj eOGQ GdaMhd aj TQM efGQ GdCUhd eY hLGRI daXg hZehV dMXg hSejJg HOGFQ GdCUhd Edi Yde GdCUhd (B--s
(3BNQgG (B:s
(3hMb GdZjQ dG jahJ eYfi dGfLHGQg HGdVeGf hdgPG Cj dHbGA GdMQeI EPG UHQ aj gPjf GdbSejf Cj GdBNQjf MJi bJd UGQ TgjOG dCfg HPd faSg dEbGeI Mb eMJQe GdMeO ddg Ydi GdEJeGe hGdTcQ Ydi GdGNJJGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/17s
(3cTa GdXfhf (B2 / 1825s
(3gOjI GdYGQajf (B2 /229s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3CUhd Gdabgs